Otomasi Trigger dengan Penentuan Sudut dalam Foto Panorama Berbasis Arduino Uno - Nur Ikhwan Sholihin; Danang Lelono (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2015)
In landscape photography, some supporting devices are needed to assign how much the camera’s shifting consistently is. It is needed to get good photos without any blank spot photos. The linked photos could be rendered to be a landscape photo using a photography software. It is could be done by image stiching, a way to stich photos taken from one constant taking point. The device is an automatic device which could assign how much the rotation degree of the camera’s head with given input, how much the shift is. It will take a shot if the rotation degree is appropriate with the given input. The system testing by variying the shift value of camera using one focal length value. The accuration test of the consistency of camera’s shift and camera’s direction. The error value could be determined by joining two parallel photo.According to the testing, tool can work automatically and also trigering can do well. Efficient shift in the number of photos and good results using the pan 9 times and tilt 4 times. The results of the error rates shift analysis have value less than 3% and that makes the tool quite stable and consistent in its movements.